International games on climate change control - Carlo Carraro; Francesca Moriconi (Fondazione Eni Enrico Mattei (FEEM), 1998)
In this paper an n-player non-co-operative game is used to model countries' decision of whether or not to sign an international agreement on climate change control. The stable coalition structure of the game is defined and then computed for a climate game in which the role of carbon leakage is also taken into account. At the equilibrium, a coalition may emerge despite the public good nature of climate. The size of the coalition depends on the degree of interdependence of countries' emission strategies, and on the type of conjectures that each country forms on the consequences of its own decision to join or to defect from the environmental coalition.
Keywords: C72; H41; Q40; Q48; 330; Climate change; Non co-operative game theory; Endogenous formation of coalition; Rational conjectures; International agreements; Umweltabkommen; Klimawandel; Spieltheorie; Koalition; Theorie